Comparative characteristics of psychophysiological and shooting performance between intermediate and elite compound archers - Txi, Mon Redee Sut (Tanjung Malim, 2023)
Comparative characteristics of psychophysiological and shooting performance between intermediate and elite compound archers by Txi, Mon Redee Sut